New Adaptive High Starting Torque Scalar Control Scheme for Induction Motors Based on Passivity - Travieso-Torres, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
A novel adaptive high starting torque (HST) scalar control scheme (SCS) for induction motors (IM) is proposed in this paper. It uses a new adaptive-passivity-based controller (APBC) proposed herein for a class of nonlinear systems, with linear explicit parametric dependence and linear stable internal dynamics, which encompasses the IM dynamical model. The main advantage of the HST-SCS includes the ability to move loads with starting-torque over the nominal torque with a simple and cost-effective implementation without needing a rotor speed sensor, variable observers, or parameter estimators. The proposed APBC is based on a direct control scheme using a normalized fixed gain (FG) to fine-tune the adaptive controller parameters. The basic SCS for induction motors (IM) and the HST-SCS were applied to an IM of 200 HP and tested using a real-time simulator controller OPAL-RT showing the achievement of the proposal goal. © 2020 by the authors.
Keywords: adaptive-passivity-based controller (APBC); scalar control scheme (SCS); induction motor (IM); proportional (P) controller; nonlinear dynamical systems